2010
DOI: 10.1590/s1516-14392010000100009
|View full text |Cite
|
Sign up to set email alerts
|

Metallic ions in organs of rats injected with metallic particles of stainless steel 316L and Ti6Al4V alloy

Abstract: Despite the interest in identifying systemic effects caused by the metallic particles released from long term metallic implants in the body, few works support reliable conclusions about the effects of those particles in organs. The aim of the present work is to look for damages in tissues of liver, kidney, lung and heart of rats submitted to injection of Hank's solution contained particles of Ti6Al4V alloy and Stainless Steel 316L, obtained by metal friction. The particles size ranges from 50 to 200 µm for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…According to previous research [ 7 ], the results showed that there were some elements of media traces on the material surface, which could affect the biocompatibility properties [ 39 , 40 ]. Therefore, this research also studied the residual elements on the surface to determine whether or not the media of the second shot would be able to stick on the surface in the manner of single shot peening, and whether elements of the first shot can be removed from the second shot or not.…”
Section: Resultsmentioning
confidence: 99%
“…According to previous research [ 7 ], the results showed that there were some elements of media traces on the material surface, which could affect the biocompatibility properties [ 39 , 40 ]. Therefore, this research also studied the residual elements on the surface to determine whether or not the media of the second shot would be able to stick on the surface in the manner of single shot peening, and whether elements of the first shot can be removed from the second shot or not.…”
Section: Resultsmentioning
confidence: 99%
“…The purpose is to eliminate the residual and unmelted powders on the surface of the original printed sample, to increase the roughness and biological function of the material, and to strengthen the integration of bone tissue and materials. However, with the increasing understanding of the mechanism of wound healing and the response of host cells to biomedical metal materials, speci c "immunoregulatory" metal materials may promote wound healing and osseointegration, which means that residual powders on the surface of 3D printed metal may not be a completely harmful factor [43,44].…”
Section: Effects Of Implant Residual Powder In Vivomentioning
confidence: 99%
“…Three input variables (X1: HNO3 concentration, X2: temperature of passivation solution, and X3: passivation time) were selected as passivation parameters. The 3 3 full factorial design with three replications was used. Real and coded values of the parameters and their levels used in the experimentation are given in previous published paper [13].…”
Section: Passivation Processmentioning
confidence: 99%
“…The main disadvantages of this steel are local corrosion susceptibility during prolonged contact with human tissue, and release of metal ions [2]. Additionally, nickel is known as a strong immunological reaction medium and may cause various health problems [3]. Despite the above listed weaknesses, SS has the ability to spontaneously form a stable self-protecting oxide layer (passive film) on its surface in the reaction with air or most aqueous environments.…”
mentioning
confidence: 99%